2021
DOI: 10.3390/en14071934
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Behaviors Regarding Environmental Protection in the Financial Decisions of Individual Consumers

Abstract: Insufficient environment protection may have serious ecological consequences, resulting in a number of problems in the modern world, many of which are a direct result of human behavior. Therefore, one needs to limit negative ecological effects by consciously shaping environment-related behaviors. The present paper analyzes the declared attitudes of individuals when it comes to taking into consideration pro-environmental factors, including energy, consumption, and waste. We have also studied the social awarenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The research also indicates that there is a statistically significant negative correlation between PEB at the country level and the proportion of households with children in total households, which on the one hand indicates that young people do not show higher PEB, but also that the countries at lower levels of economic development have a higher proportion of households with children. No correlation, however, has been found between PEB and the number of women per 100 men, which is consistent with the results of studies showing that men and women manifest similar pro-environmental behaviour [21].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The research also indicates that there is a statistically significant negative correlation between PEB at the country level and the proportion of households with children in total households, which on the one hand indicates that young people do not show higher PEB, but also that the countries at lower levels of economic development have a higher proportion of households with children. No correlation, however, has been found between PEB and the number of women per 100 men, which is consistent with the results of studies showing that men and women manifest similar pro-environmental behaviour [21].…”
Section: Resultssupporting
confidence: 88%
“…This study differs from the existing research in two fundamental aspects, both of which concern the assessment of pro-environmental behaviour. Most empirical studies have so far taken into account individual types of behaviour, such as separate waste collection [19], energy conservation [20], or the generally understood pro-environmental behaviour [21]. In this study, pro-environmental behaviour includes several aspects, including the use of renewable energy, waste separation, and the use of public transport.…”
Section: Introductionmentioning
confidence: 99%
“…To some extent at least, the methods presented in this article can provide answers for these dilemmas, given the way they bring the desired effects when it comes to both social dialogue and the implementation of GeoDesign. There is also some kind of antidote offered to the not-very-optimistic research results presented by Walczak et al [62], with the difference being that the main interest in eco-innovation and research in this context is being shown by local government.…”
Section: Discussionmentioning
confidence: 99%
“…However, the early nature of the stage reached in Poland when it comes to developing eco-innovation gains confirmation in the research, as does the limited level of public involvement in pro-environmental initiatives [62]. While a diversified market characterising recipients allows relatively low prices to be maintained, these should depend more and more on implemented innovation allowing wastes to be used as raw materials.…”
Section: Pull 1ststage Of Research Desk-research Stage Pull Nthstage ...mentioning
confidence: 99%
“…The availability and possibility of using electricity to meet the needs of households have gradually become a criterion for determining their level of well-being. Since a large part of cultural programs is broadcasted through video and audio media, electricity indirectly plays an important role in promoting the cultural level of society [5].…”
Section: Introductionmentioning
confidence: 99%